Gambaran dan Nilai Rata-rata Prostate Specific Antigen Pasien yang dilakukan Transurethral Resection of the Prostate di RSUD Dr. Achmad Mochtar Bukittinggi - Muhammad Fachriza Busril; Etriyel MYH; Meinapuri M; Alvarino Alvarino; Mulyani H; Novita E (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Prostate-specific antigen (PSA) is a serine protease produced by the prostate epithelium. PSA is a product of prostate epithelial cells that functions to liquefy semen, thereby enhancing sperm motility. This study is an analytical study with a cross-sectional design, utilizing secondary data from the medical records of patients who underwent transurethral resection of the prostate (TURP) at Dr. Achmad Mochtar General Hospital, Bukittinggi, from 2022 to 2023. The results of the study showed that the most commonly found PSA range category was 4-20 ng/ml, with a percentage of 40.2%. Furthermore, the study found that the highest average PSA levels were observed in patients with prostate cancer, with a mean value of 53.39 ng/ml. Based on these findings, it can be concluded that monitoring PSA levels plays a crucial role in the early diagnosis and management of prostate cancer and can serve as an important reference in future prevention and treatment efforts.